Studi Implementasi Pendekatan Pembelajaran Berbasis TPACK untuk Meningkatkan Kompetensi Murid - Pulungan, Tondy Natama; Muntamah; Kuswantara, Hary; Siswanto, Deny Hadi (Prodi PGMI STAI Sabili Bandung, 2024)
The use of technology in education has a crucial role and is very much in line with the progress of the times. Technology offers various information needed in the learning process. One approach that optimally utilizes technology in learning is TPACK. The objectives of this study are to (1) Describe the learning process that integrates TPACK; (2) Identify the challenges and steps taken in implementing TPACK-based learning; (3) Present the results of TPACK learning at Perumnas 3 State Elementary School. This study uses a qualitative approach with a descriptive method, collecting data through observation documentation and interviews in the form of sentences. The results of this study are: (1) TPACK can be a technology-based learning approach that can adapt to the development of the times (2) The implementation of TPACK requires the support of learning facilities such as laptops, cellphones, projectors, learning videos, and internet connections; (3) TPACK-based learning has a positive impact on improving students' skills in understanding material and using technology